Construct validity and inter-rater reliability of the Gymnastic Functional Measurement Tool in the classification of female competitive gymnasts in Canada - Kaldas, J.; Bisson, C.; Hogue, A.-C.; Apinis, C.; Berbiche, D.; Gaudreault, N. (Physical Therapy in Sport, 2017)
Objectives: To determine the construct validity and the inter-rater reliability of the Gymnastic Functional Measurement Tool (GFMT) within the parameters of the Canadian classification of female competitive gymnasts. Design: Validity and Reliability study. Setting: The GFMT was administered by evaluators who had no previous knowledge of the competing level of the gymnasts. To determine the construct validity, a multiple linear regression analysis was carried out between the GFMT scores and the gymnasts` competition level to obtain the coefficient of determination. To estimate the inter-rater reliability, gymnasts were simultaneously evaluated by two evaluators. Intraclass correlation coefficient (ICC) analysis was carried out for the individual score of each item as well as for the total score of the GFMT. Participants: Ninety (90) female gymnasts aged between the ages of 8 and 18 years old. Main outcome: GFMT total score and individual score of each item. Results: The study demonstrated an excellent relationship between the total GFMT scores and the gymnasts` competition level (r2 = 0.97). The inter-rater reliability analysis of the GFMT total score was excellent with an ICC of 0.98. Conclusion: Construct validity and inter-rater reliability of the GFMT in the classification of female competitive gymnasts in Canada has been demonstrated.